2020
DOI: 10.32861/sr.66.48.52
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Coliform Bacterial Load of Some Drinking Water Sources in Dutse Metropolis of Jigawa State Nigeria

Abstract: Drinking water samples from 5 sachet water companies, 3 boreholes and 2 taps, collected from different locations of Dutse Metropolis of Jigawa State, Nigeria were analysed for coliform bacterial counts using the Membrane Filtration Technique. All the samples contained some amounts of total coliforms, but mostly within permissible levels. Thirty three percent (33%) of the samples from borehole, 60% from sachet water and 100% from the taps contained faecal coliforms, which indicates contamination. Cultures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Other countries with higher prevalence were 20.0% in Saudi Arabia [ 4] , 17.1% in Yemen [15] , 25.9% in Tajikistan [16] , and 18% in Tanzania [17] . In Nigeria several studies have reported prevalence ranging from as low as 0.1% to values as high as 67.6% [11,12,18,19] . The difference between most of these studies and ours is the fact that most of them were based on a population subset, and some included clinical manifestation unlike ours that reviewed the parasitology records of an undifferentiated hospital population.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries with higher prevalence were 20.0% in Saudi Arabia [ 4] , 17.1% in Yemen [15] , 25.9% in Tajikistan [16] , and 18% in Tanzania [17] . In Nigeria several studies have reported prevalence ranging from as low as 0.1% to values as high as 67.6% [11,12,18,19] . The difference between most of these studies and ours is the fact that most of them were based on a population subset, and some included clinical manifestation unlike ours that reviewed the parasitology records of an undifferentiated hospital population.…”
Section: Discussionmentioning
confidence: 99%